Kounis Syndrome Secondary to Laxative Administration - Mateo Zuluaga-Gómez; Daniel González-Arroyave; Carlos M. Ardila (Case Reports in Medicine)
Kounis syndrome (KS) is defined as an acute coronary syndrome triggered by the release of inflammatory mediators after an allergic attack. It usually occurs secondary to allergic injuries from foods, medications, and insect bites. However, there are no known reports of KS secondary to the intake of laxatives. This article reports the case of a 43-year-old woman who, after ingesting a dose of sodium phosphate monobasic/sodium phosphate dibasic, presented a maculopapular rash on the trunk and extremities. The electrocardiogram showed ST depression in V4-V5-V6 and signs of prolonged QTc; troponin I uptake was positive. Due to presumed myocardial injury and high suspicion of coronary disease, coronary angiography was requested, which showed epicardial coronary arteries, without angiographically significant stenosis, thus confirming the presence of KS secondary to the ingestion of a laxative.